On the Asymmetry of the Nexus between Governance and Environmental Pollution - Aziz, Leila Taleb Marandi; Moghaddasi, Reza; Moosavi, Nematollah (International Journal of Energy Economics and Policy, 2023)
Governance has attracted the attention of researchers as a multifaceted and effective variable in the economic performance of countries during last three decades. On the other hand, with the intensification of environmental concerns of governments, the analysis of the relationship between governance and the worsening of environmental sustainability indicators, such as the volume of pollutant emissions, has also become one of the study primacies of environmental economists. The present study aimed to investigate the aforesaid relationship for a group of developing and developed countries for the period 1990 to 2020. To this end, the Nonlinear Autoregressive Distributed Lag (NARDL) model based on panel data was used, which permits examination of the existence of non-linear relationships between variables. Main results show asymmetry in the magnitude of the effects of governance indicators on carbon dioxide emissions in developed and developing countries as the coefficient of the positive shock to economic governance for developed countries (0.52) is almost twice that of developing nations (0.27). We found that economic governance enhancement has a stronger impact on reducing environmental pollution and thus protecting the environment.